Accuracy of different impression materials in parallel and nonparallel implants - Mahroo Vojdani; Kianoosh Torabi; Elham Ansarifard (Wolters Kluwer Medknow Publications, 2015)
Background: A precise impression is mandatory to obtain passive fit in implant-supported prostheses. The aim of this study was to compare the accuracy of three impression materials in both parallel and nonparallel implant positions. Materials and Methods: In this experimental study, two partial dentate maxillary acrylic models with four implant analogues in canines and lateral incisors areas were used. One model was simulating the parallel condition and the other nonparallel one, in which implants were tilted 30° bucally and 20° in either mesial or distal directions. Thirty stone casts were made from each model using polyether (Impregum), additional silicone (Monopren) and vinyl siloxanether (Identium), with open tray technique. The distortion values in three-dimensions (X, Y and Z-axis) were measured by coordinate measuring machine. Two-way analysis of variance (ANOVA), one-way ANOVA and Tukey tests were used for data analysis (α = 0.05). Results: Under parallel condition, all the materials showed comparable, accurate casts (P = 0.74). In the presence of angulated implants, while Monopren showed more accurate results compared to Impregum (P = 0.01), Identium yielded almost similar results to those produced by Impregum (P = 0.27) and Monopren (P = 0.26). Conclusion: Within the limitations of this study, in parallel conditions, the type of impression material cannot affect the accuracy of the implant impressions; however, in nonparallel conditions, polyvinyl siloxane is shown to be a better choice, followed by vinyl siloxanether and polyether respectively.